Use of iliac crest allograft for Dega pelvic osteotomy in patients with cerebral palsy - Sung, Ki Hyuk; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Kim, Jaeyoung; Park, Moon Seok (BMC Musculoskeletal Disorders, 2018)
Background: Dega pelvic osteotomy is commonly performed procedure in patients with cerebral palsy (CP) undergoing hip reconstructive surgery for hip displacement. However, there has been no study investigating the outcomes after Dega pelvic osteotomy using allograft in patients with CP. This study investigated the outcomes of Dega pelvic osteotomy using iliac crest allograft in CP with hip displacement and the factors affecting allograft incorporation. Methods: This study included 110 patients (150 hips; mean age 8y7mo; 68 males, 42 females) who underwent hip reconstructive surgeries including Dega pelvic osteotomy using iliac crest allograft. To evaluate the time of allograft incorporation, Goldberg score was evaluated according to the follow-up period on all postoperative hip radiographs. The acetabular index, migration percentage, and neck-shaft angle were also measured on the preoperative and postoperative follow-up radiographs. Results: The mean estimated time for allograft incorporation (Goldberg score ≥ 6) was 1.1 years postoperatively. All hips showed radiographic union at the final follow-up and there was no case of graft-related complications. Patients with Gross Motor Function Classification System (GMFCS) level V had 6.9 times higher risk of radiographic delayed union than those with GMFCS level III and IV. Acetabular index did not increase during the follow-up period (p = 0.316). Conclusions: Dega pelvic osteotomy using iliac crest allograft was effective in correcting acetabular dysplasia, without graft-related complications in patients with CP. Furthermore, the correction of acetabular dysplasia remained stable during the follow-up period.
Keywords: Acetabulum; Adolescent; Allografts; Bone Transplantation; Cerebral Palsy; Child; Child, Preschool; Female; Follow-Up Studies; Hip Dislocation; Hip Joint; Humans; Ilium; Male; Osteotomy; Postoperative Complications; Radiography; Reconstructive Surgical Procedures; Retrospective Studies; Time Factors; Treatment Outcome; Aceteabular dysplasia; Cerebral palsy; Dega osteotomy; Goldberg score; Iliac crest allograft